A study of micro vascular complications and associated risk factors in newly diagnosed patients of type 2 diabetes mellitus - Prakash, Bharti; Yadav, Laxmi K. (International Journal Of Community Medicine And Public Health, 2018)
Background: Diabetes and its complications are one of the leading causes of death and disability worldwide. The aim of the study is to elucidate the prevalence and associated risk factors of microvascular complication among diabetes mellitus type 2 population of Ajmer, Rajasthan India. Methods: This is the study of 464 newly detected type 2 diabetic people screened for their biochemical parameters, attending outpatient department comprising of 256 male and 208 female. The presence of complications was evaluated by relevant investigations. Results: Microvascular complication namely retinopathy was diagnosed in 344 (74%) of type 2 diabetic patients, neuropathy in 200 (43%), nephropathy in 138 (30%). Linear regression analysis concluded that age, body mass index, duration, family history, stress, glycated haemoglobin (HbA1C), triglyceride and total cholesterol were significantly associated with these vascular complications. Prevalence of microvascular complications increases with age, duration, body mass index (BMI), hereditary and poor glycemic control. Conclusions: Retinopathy and neuropathy were the most prevalent microvascular complication in type 2 diabetic population.